Fraud analytics using descriptive, predictive, and social network techniques : a guide to data science for fraud detection - Baesens, Bart; e uthor; Verbeke, Wouter, 1983- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2015)
Early detection is a key factor in mitigating fraud damage, but it involves more specialized techniques than detecting fraud at the more advanced stages. This invaluable guide details both the theory and technical aspects of these techniques, and provides expert insight into streamlining implementation. --
Fraud: detection, prevention, and analytics! -- Data collection, sampling, and preprocessing -- Descriptive analytics for fraud detection -- Predictive analytics for fraud detection -- Social network analysis for fraud detection -- Fraud analytics: post-processing -- Fraud analytics: a broader perspective.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
English.
John Wiley and Sons
Keywords: Fraud -- Statistical methods; Fraud -- Prevention; Commercial crimes -- Prevention; Fraude; SOCIAL SCIENCE -- Criminology; Commercial crimes -- Prevention; Fraud -- Prevention